The Influence of Intellectual Capital on the Financial Performance of Cosmetics Manufacturing Manufacturing Companies in the Indonesia Stock Exchange in 2013 - 2018 - Winanti Ita Aflakhah; Sigit Hermawan (Indonesian Journal of Law and Economics Review, 2019)
This study aims to know the effect of human capital coefficient, structural capital efficiency coefficient, and capital employed efficiency coefficient partially and simultaneously on the performance of manufacturing companies in Indonesia Stock Exchange. This study uses a quantitative, causal approach. The sampling technique uses saturated sample technique. The researcher uses secondary data, namely the company's financial statements obtained from the official website of IDX. Methods of collecting data include literature studies and indirect observations. The analysis technique uses multiple linear regression analysis, classical assumption test, and model feasibility test, the researcher tests the hypothesis by using the T test and F test. The results of this study indicate that (1) Human Capital Coefficient partially influences the performance of the company in the stock market. Indonesian securities. (2) Structural Capital Efficiency Coefficient of coefficient is partially influential on the performance of company companies manufacturing on IDX (3) Capital Employed Efficiency Coefficient partially influences the performance of company companies manufacturing on IDX. (4) Human Capital Coefficient Capital Employed, Structural Capital Efficiency Coefficient, and Efficiency Coefficient simultaneously influence the performance of manufacturing companies in the IDX.